Use of Fall Cone Test for the determination of undrained shear strength of cohesive soils - Canelas Diogo; Fernandes Isabel; Lopes Maria da Graça (MATEC Web of Conferences, 2018)
CT156, Geotechnics and civil engineering, has been developing efforts to create standards with the generic designation EN ISO 17892, Geotechnical investigation and testing - Laboratory testing of soil. The recent publication of EN ISO 17892-part 6, Fall Cone Test which describes in detail the use of this test method to estimate the undrained shear strength of cohesive soils leads to the necessity for the laboratories to get familiar with this test method and to acquire the required sensibility to analyse the results obtained. Originally designed to determine the liquid limit of fine soils, for which purpose it is considered as an accurate substitute of the Casagrande method, the method may constitute an alternative to the direct shear test, which takes certainly longer time to be carried out and is more complex. The present work aims to compare the values for liquid limit obtained with the Casagrande's method and the cone method and as well as the use of this test to estimate undrained shear strength, correlating with results from other laboratory tests such as the Direct Shear Test and the Laboratory Vane Test on remoulded samples. The results obtained show that there is a good correlation between the applied test methods for determination of the liquid limit and that, for some water contents, the results obtained by the three test methods are comparable.